Venous Manometry as an Adjunct for Diagnosis and Multimodal Management of Intracranial Hypertension due to Meningioma Compressing Sigmoid Sinus - Cheyuo, Cletus (Cureus, 2019)
Intracranial venous hypertension is a rare presentation of meningiomas in the transverse-sigmoid sinus region. We describe a case of a young patient presenting with intracranial hypertension due to a meningioma causing compression of the dominant sigmoid sinus. We were able to document the cerebral venous pressure gradient across the lesion confirming our hypothesis that compression of the sigmoid sinus from the meningioma was the cause of intracranial hypertension. The patient is a 17-year-old male who presented with intracranial hypertension due to meningioma at the right dominant sigmoid sinus, which was treated by a Simpson grade IV surgical resection followed by stereotactic radiosurgery. Following treatment, his papilledema resolved and he remains symptom-free at 18 months. In conclusion, venous manometry is a useful adjunct to diagnose intracranial hypertension in non-idiopathic causes of intracranial hypertension. A multimodal management approach of intracranial hypertension due to outflow obstruction from the dominant sinus led to an excellent recovery on follow up.